Perancangan Media Informasi Augmented Reality Wihara Kstigarbha Bodhisattva Tanjungpinang - Handayani, Nadhila; Sudiani, Yoni; Rajab, Junaidi (Institut Seni Indonesia Padangpanjang, 2024)
Ksitigarbha Bodhisattva Temple is a place of Buddhist worship and has become a religious and cultural tourist spot in the Riau Islands, Tanjungpinang. The statues at the Ksitigarbha Bodhisattva Temple only display information in Mandarin, even though the tourists who visit there mostly come from outside the area, not even just Buddhists. From interviews with visitors who came to the temple, they stated that apart from getting interesting photos, they also wanted to know what the Ksitigarba Bodhisattva Temple was like. However, due to the lack of communicative information, tourists do not know the information written in Mandarin. So